2017
DOI: 10.4172/2155-6156.1000725
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Life in Children with Type I Diabetes Mellitus (T1D) in Minia Governorate: Relationship with Mood and Family Attitudes

Abstract: Introduction: Children with T1D experience behavioral difficulties and lower social competency compared with healthy children. Quality of life is considered to be a significant indicator of disease prognosis. Aim:To evaluate the health related quality of life of children with T1D, and how much it could be affected by their mood and family attitudes and to study the relationship between these variables and the metabolic control of the diabetic children.Methods: 72 children with T1D were included and subjected t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 30 publications
2
6
0
Order By: Relevance
“…The reduction in a large number of the items resulted in a slightly negative impact on the items' reliability. Similar observation was made with the separation values, although, all index values were within acceptable limits (Bond and Fox, 2015), which could be a proof that the measures have the ability to distinguish the items into two or more distinct groups, despite the low index values (Kook and Varni, 2008). The low separation index values of the items might partly be influenced by the sample size of the study population, although, it has been reported that small sample could be enough for validity analysis of instrument using Rasch measurement model (Bond and Fox, 2015), which was evident in the item reliability and separation index values for knowledge.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…The reduction in a large number of the items resulted in a slightly negative impact on the items' reliability. Similar observation was made with the separation values, although, all index values were within acceptable limits (Bond and Fox, 2015), which could be a proof that the measures have the ability to distinguish the items into two or more distinct groups, despite the low index values (Kook and Varni, 2008). The low separation index values of the items might partly be influenced by the sample size of the study population, although, it has been reported that small sample could be enough for validity analysis of instrument using Rasch measurement model (Bond and Fox, 2015), which was evident in the item reliability and separation index values for knowledge.…”
Section: Discussionsupporting
confidence: 82%
“…Mutatis mutandis, there were observed increment in persons' reliability measures to 0.64, 0.61, and 0.70 for KAP, respectively (Table 4) compared to those in the draft scale ( Table 2). The separation index values were also in the range of > 1, but < 2, which were indications of the levels of consistency in the respondent behavior, hence, it was an indication of the instruments' capability of differentiating between high and low-performance abilities of respondents (Kook and Varni, 2008;Bond and Fox, 2015). As a measure of consistency in behaviors, it implied that lapses made by the respondents were likely to affect the separation index value negatively, meaning that increasing sample size further might lead to a possible decrease in the index value (Bond and Fox, 2015).…”
Section: Discussionmentioning
confidence: 95%
“…However, when the Spearman correlation test was conducted, none of the functions and the quality of life were statistically had a significant correlation with HbA1C level (r = 0.264, p > 0.05). This is in line with the research conducted by Ali et al (Egypt) which states that the PedsQL domain shows no significant difference between children with good controls and poor controls T1DM (p > 0.05 for all domains) [21]. Consistent with previous research, Emmanouilidou (Greece) conducted a study on 89 children with T2DM also explained that there was no difference between HbA1C and the quality of life of children with T1DM [22].…”
Section: The Relationship Between Hba1c and The Quality Of Life Of Children With T1dmsupporting
confidence: 91%
“…Literature has shown debating findings of either no significant correlations between the 2 or revealed a negative relationship, that is, achieving better glycemic control could be at the expense of reasonable QoL especially when tackling the task from parents' versus children's perspectives. 6,11,12 This study compared the QoL scores reported by Saudi children with T1D with the reports from their parents. It also shows the correlation between glycemic control and the total aggregate and domain-specific QoL scores reported by parents and children at different developmental age groups.…”
Section: -12 Yearsmentioning
confidence: 99%